Innovative Approaches to Water Quality Assessment: Integrating Physicochemical and Biological Indicators in Forest Eco-Park Upstream Rivers - Ali, Nurul Amni; Jahani, Aqilah Zakiah; Mohd Kamil, Nor Amani Filzah; Hamzah, Nurhidayah (International Journal of Sustainable Construction Engineering and Technology, 2025)
Measuring the Water Quality Index (WQI) is essential for evaluating water conditions, especially in ecologically sensitive areas. However, assessing physicochemical indicators alone may not provide sufficient information about the overall health of river ecosystems. This study integrates macroinvertebrates as biological indicators to complement traditional WQI assessments, offering a more holistic and ecologically meaningful understanding of water quality. The research was conducted at upstream rivers in four forest eco-parks: Forest Eco-Park Soga Perdana Hill (FESP), Forest Eco-Park Mount Lambak (FEML), Forest Eco-Park Mount Pulai II (FEMP), and Forest Eco-Park Bantang River (FEBR), Johor, Malaysia. Conventional WQI parameters—including Ammonia Nitrogen (AN), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Dissolved Oxygen (DO), Total Suspended Solids (TSS), and pH—were compared with macroinvertebrate-based bioassessment using the Biological Monitoring Working Party–Average Score Per Taxon (BMWP-ASPT) index. Data analysis using Microsoft Excel showed a strong inverse correlation between BMWP-ASPT and WQI (R² = 0.9385; Pearson r = -0.93974). While WQI classified FEBR as slightly polluted (WQI = 73.77, Class III), BMWP-ASPT indicated cleaner conditions (8.04), suggesting that macroinvertebrate-based methods may reveal different ecological insights, particularly in areas with subtle anthropogenic pressures. These findings have practical implications for sustainable water management, especially in recreational eco-parks and data-limited settings, where the integration of biological and physicochemical indicators can support more comprehensive and adaptive monitoring practices.